Long‐term outcomes of breast reconstruction and the need for revision surgery. Issue 9 (10th August 2021) - Finlay, Ben; Kollias, Victoria; Hall, Kelly A.; Clement, Zackariah; Bingham, Janne; Whitfield, Robert; Kollias, James; Bochner, Melissa
Abstract: Background: Breast reconstruction (BR) often forms part of a patient's breast cancer journey. Revision surgery may be required to maintain the integrity of a BR, although this is not commonly reported in the literature. Different reconstructive methods may have differing requirements for revision. It is important for patients and surgeons to understand the factors leading to the need for revision surgery. Methods: This retrospective cohort study analyses BRs performed by oncoplastic breast surgeons in public and private settings between 2005 and 2014, with follow‐up until December 2018. Surgical and patient factors were examined, including types of BR, complications and reasons for revision surgery. Results: A total of 390 women with 540 reconstructions were included, with a median follow‐up of 61 months. Twenty‐eight percent (151/540) of reconstructions required at least one revision operation. Overall, implant‐based reconstructions (direct‐to‐implant [DTI] and two‐stage expander‐implant) had a higher revision rate compared to pedicled flap reconstructions (odds ratio 1.91, 95% confidence interval 1.08, 3.38). DTI reconstructions had the highest odds, and pedicled flap without implants the lowest odds of requiring revision. Post‐reconstruction radiotherapy increased the chance of revision surgery, while pre‐reconstruction radiotherapy did not. Odds of revision were higher in implant‐based reconstructions compared to pedicled flap reconstructions that had radiotherapy. Other factors increasing the rates of revision surgery were being a current smoker and post‐operative infection. Conclusion: Almost one‐third of reconstructive patients require revision surgery. Autologous pedicled flap reconstructions have lower rates of revision compared to implant‐based reconstructions. Radiotherapy increases the need for revision surgery, particularly in implant‐based reconstructions. Abstract : A considerable proportion of reconstructive patients require revision surgery. Pedicled flap‐based reconstructions have lower rates of revision compared to implant‐based reconstructions. Radiotherapy increases the need for revision surgery, particularly in implant‐based reconstructions.